2017
DOI: 10.1021/acs.est.7b01039
|View full text |Cite
|
Sign up to set email alerts
|

Stable Mercury Isotopes in Polished Rice (Oryza sativa L.) and Hair from Rice Consumers

Abstract: Mercury (Hg) isotopic signatures were characterized in polished rice samples from China, U.S., and Indonesia (n = 45). Hg isotopes were also analyzed in paired hair samples for participants from China (n = 21). For the latter, we also quantified the proportion of methylmercury intake through rice (range: 31–100%), and the weekly servings of fish meals (range: 0–5.6 servings/weekly). For these participants, 29% (n = 6) never ingested fish, 52% (n = 11) ingested fish < twice/weekly, and 19% (n = 4) ingested fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 40 publications
3
21
0
Order By: Relevance
“…Blood (~0.5 g) was digested in 4 mL of hydrochloric acid (HCl) and 1 mL of nitric acid (HNO 3 ) overnight. For stool, meconium, and hair samples, hot digestion was used (Rothenberg et al, 2016(Rothenberg et al, , 2017. Stool (~0.75 g) and meconium (~1.2 g) were digested in 5 mL of freshly prepared sulfuric acid (H 2 SO 4 ):HNO 3 [3:7 (v/v)], while hair (~0.02 g) was digested in HNO 3 :HCL [(3:1 (v/v)].…”
Section: Laboratory Analysesmentioning
confidence: 99%
“…Blood (~0.5 g) was digested in 4 mL of hydrochloric acid (HCl) and 1 mL of nitric acid (HNO 3 ) overnight. For stool, meconium, and hair samples, hot digestion was used (Rothenberg et al, 2016(Rothenberg et al, , 2017. Stool (~0.75 g) and meconium (~1.2 g) were digested in 5 mL of freshly prepared sulfuric acid (H 2 SO 4 ):HNO 3 [3:7 (v/v)], while hair (~0.02 g) was digested in HNO 3 :HCL [(3:1 (v/v)].…”
Section: Laboratory Analysesmentioning
confidence: 99%
“…In adjusted models, recent consumption of rice and/or mixed rice dishes was associated with THg and MeHg among seafood consumers and mixed rice dishes were associated with THg and UHg among non-seafood consumers. Numerous studies have been able to quantify mercury concentrations of concern in rice and rice-containing cereals ( 29 , 30 , 56 58 ). Several studies have also identified significant associations of rice with mercury biomarker concentrations or modeled mercury exposures in populations with substantial seafood consumption ( 33 , 59 ), although an analysis of the Korean Health and Nutrition Examination Survey did not observe an association between blood mercury and rice consumption ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The larger fraction of iHg or the smaller %MeHg in the consumed food, the greater the MDF offsets could be. 13 , 99 This highlights the importance of incorporating Hg speciation of both human biomarkers and exposure sources when interpreting δ 202 Hg in human biomarkers.…”
Section: Mercury Isotope Dynamics In Biotamentioning
confidence: 99%